Unveiling and Characterizing Early Bilateral Interactions between Biofilm and the Mouse Innate Immune System - Forestier, Christiane; Billard, Elisabeth; Milon, Geneviève; Gueirard, Pascale (Frontiers in Microbiology, 2017)
A very substantial progress has been made in our understanding of infectious diseases caused by invasive bacteria. Under their planktonic forms, bacteria transiently reside in the otherwise sterile mammal body tissues, as the physiological inflammation insures both their clearance and repair of any tissue damage. Yet, the bacteria prone to experience planktonic to biofilm developmental transition still need to be studied. Of note, sessile bacteria not only persist but also concur preventing the effectors and regulators of the physiological inflammation to operate. Thus, it is urgent to design biologically sound experimental approaches aimed to extract, at the earliest stage, immune signatures of mono-bacteria planktonic to biofilm developmental transition in vivo and ex vivo. Indeed, the transition is often the first event to which succeeds the “chronicization” process whereby classical bacteria-targeting therapies are no more efficacious. An in vivo model of micro-injection of Staphylococcus aureus planktonic or biofilm cells in the ear pinna dermis of laboratory transgenic mice with fluorescent immune cells is proposed. It allows visualizing, in real time, the range of the early interactions between the S. aureus and myeloid cell subsets- the resident macrophages and dendritic cells, the recruited neutrophil granulocytes/polymorphonuclear neutrophils, monocytes otherwise known to differentiate as macrophages or dendritic cells. One main objective is to extract contrasting immune signatures of the modulation of the physiological inflammation with respect to the two bacterial lifestyles.